Homem da meia noite - Santagostino, Paolo (Italy : Santagostino, Paolo, 2007)
“Olinda” is one of the best-preserved colonial cities in Brazil and it is the protagonist of this short documentary. Its contrasting vitality is revealed from the elegant movements of the ‘Frevo’ dancers to the piles of trash gathered in the streets during sunset, from the children playing barefoot in front of churches to the chaotic ladeiras full of people and in the colorful “blocos” and “bonecos”.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films